Finite State Automata pada Vending Machine Pembuat Teh Otomatis - Virda Mega Ayu; Windu Gata; Jordy Lasmana Putra; Frieyadie; Hafifah Bella Novitasari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Vending machines are one form of technological development. In Indonesia, the type that is often found is a vending machine, a type of soft drink with several choices. Seeing the business opportunities that exist in the contemporary beverage sector, in this research, Finite State Automata (FSA) is applied to automatic tea-making vending machines. FSA is a mathematical model that can accept input and output from the same State. This automatic tea vending machine can produce 6 types of tea and 4 choices of toppings as a complement. This vending machine is equipped with upsize glass facilities from medium to large sizes. For payment, this vending machine provides cash and Cashless options. In the application of the FSA concept, this study conducted a State FSA trial using JFLAP. So that with the application of the FSA concept, it becomes one of the alternatives in designing an automatic tea making vending machine.